2023
DOI: 10.1021/acsomega.2c07280
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy Mediated by AMPK/DDiT4/mTOR Axis in HT22 Cells Under Oxygen and Glucose Deprivation/Reoxygenation

Abstract: Background: cerebral ischemia/reperfusion (I/R) injury is an important complication of ischemic stroke, and autophagy is one of the mechanisms of it. In this study, we aimed to determine the role and mechanism of autophagy in cerebral I/R injury. Methods: the oxygen and glucose deprivation/reoxygenation (OGD/R) method was used to model cerebral I/R injury in HT22 cells. CCK-8 and LDH were conducted to detect viability and damage of the cells, respectively. Apoptosis was measured by flow cytometry and Tunel sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“… 40 Furthermore, the expression of AMPK, BECLIN-1, and ATG5 proteins enhances and inhibits the mTOR protein involved in the induction of autophagy in cardiovascular diseases. 41 43 The study suggests that ketamine treatment and its combination with insulin ameliorated the altered expression of mTOR, AMPK, BECLIN-1, and ATG5 protein in myocardial tissues of I/R-induced myocardial injury in DM2. Our findings were further supported by the study report, 42 where autophagy-associated signaling pathways such as AMPK/mTOR were suggested to play a crucial role in protecting against myocardial ischemia-reperfusion injury in diabetes mellitus (DM).…”
Section: Discussionmentioning
confidence: 96%
“… 40 Furthermore, the expression of AMPK, BECLIN-1, and ATG5 proteins enhances and inhibits the mTOR protein involved in the induction of autophagy in cardiovascular diseases. 41 43 The study suggests that ketamine treatment and its combination with insulin ameliorated the altered expression of mTOR, AMPK, BECLIN-1, and ATG5 protein in myocardial tissues of I/R-induced myocardial injury in DM2. Our findings were further supported by the study report, 42 where autophagy-associated signaling pathways such as AMPK/mTOR were suggested to play a crucial role in protecting against myocardial ischemia-reperfusion injury in diabetes mellitus (DM).…”
Section: Discussionmentioning
confidence: 96%
“…A previous study by Zhang et al reported that the expression of DDIT4 was increased significantly along with activated autophagy induced by oxygen and energy deprivation in HT22 cells (a neuronal line of mouse hippocampus), and could be further increased by treatment with the AMPK activator AICAR. 60 Therefore, we speculated that phenformin, another AMPK activator, induced DDIT4 and/or NIBAN1 through the activation of AMPK in OSCC cells. However, the inhibition of AMPK expression by the siRNA mediated knockdown of AMPK α1 and α2 did not block the increased expression of DDIT4 or NIBAN1 in phenformin-treated OSCC cells, indicating that phenformin promotes DDIT4 and NIBAN1 expression in an AMPK-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Materials:The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/ijms241512164/s1. References[64,[86][87][88][89][90][91][92][93] are cited in the supplementary materials.…”
mentioning
confidence: 99%